Psychoemotional State of Boarding School Pupils and their Rehabilitation in Health Center «Pivdennoberezhny» (Alupka) - L.V. Pypa; S.V. Rymsha; A.V. Filyk; I.L. Lukyanovych; Yu.M. Lysytsya; M.V. Murdyd; S.V. Breus; V.M. Zamoroka (Zaslavsky O.Yu., 2012)
The article deals with features of anxiety following rehabilitation restorative treatment in children with familial deprivation. Convalescent facilities in health center «Pivdennoberezhny», including climato-, balneo-, halo-, phyto-, aromatherapy and massage under the control of clinical blood analysis, ECG, study of respiratory function, WAM and Spielberger psychodiagnostic tests, were effective, what can be assessed by improvement of the results of all studies. The need for continuation of rehabilitation and recovery measures, as well as psychotherapeutic effect, is also practically assured, it is necessary for amelioration and prevention of psychosomatic disorders in children with familial deprivation.